Facilitating the socio-economic approach to management : results of the first SEAM conference in North America - Savall, Henri; Conbere, John; Heorhiadi, Alla; Cristallini, Vincent; Buono, Anthony F. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
This book is the 20th volume in the Research in Management Consulting series and the sixth major collaboration with Henri Savall, Véronique Zardet, and their team of intervenerresearchers from the Socio-Economic Institute for Firms and Organizations (ISEOR) in LyonÉcully, France. In 2013, for the first time, ISEOR co-sponsored a conference on its Socio-Economic Approach to Management (SEAM) paradigm and methodology in the United States. The volume captures the ideas, applications, and exchanges of that meeting hosted by the University of St. Thomas in Minneapolis, Minnesota. The book attempts to bring the reader into the conference itself. The different chapters include the contributors' presentations ("Chapter Prologue: Conference Remarks"), revised conference papers, and the question and answer dialogue for the session. For those interested in delving further into the SEAM approach, the volume also contains a general bibliography on the development, critique, and application of the framework.
Conference proceedings.
Keywords: Management -- Social aspects.; Management -- Economic aspects.; Business & Economics -- Management.; Consultancy.; Management and management techniques.; elektronické knihy; electronic books